TCS CLL Resource pack term 2 (KG) (The City School Lahore)
In Term 2, Kindergarten students continued to build foundational skills in Communication, Language, and Literacy through a variety of engaging, age-appropriate activities.
Develop foundational communication, language, and literacy skills through storytelling, phonological awareness, vocabulary development, speaking, listening, and early writing tasks.
Shelving location: M4
The Communication, Language, and Literacy (CLL) curriculum for Kindergarten Term 2 is thoughtfully designed for children aged 4 to 5 years who are in the early stages of developing foundational language and communication skills. At this stage, learners are rapidly expanding their vocabulary, developing phonemic awareness, and beginning to express their thoughts, feelings, and ideas more clearly through both spoken and emerging written language.
Keywords: TCS CLL Resource Pack